Effect of pre-starter diet supplemented with high energy and moisture on growth performance of broiler chicken - Hashim, Muhamad Nuraiman (2016)
Feed cost is the highest cost in the production of poultry, up to 70% of the total cost. A day reduced in rearing can save money from feeding cost especially in commercial farm where a large number of chicken are reared. Day old chicks have to go through a major shift of metabolic dependence from endogenous lipid-rich yolk to feed on exogenous carbohydrate and protein-rich feed. Pre-starter diet in highly digestible form may affect not only early development and growth of broiler chicken but also the performance at the end of rearing period thus optimizing their genetic potential for growth. The present study was conducted to investigate the effect of pre-starter diet with energy supplementation and diet with moisture on the body weight, feed conversion ratio (FCR), and carcass characteristic (weight of organs and fat) of broiler chicken. Sixty day-old Cobb 500 male broiler chicks were randomly assigned to four treatments with three replications, with five chickens in each replicate, for 42 days. The chicks were reared in cages. Treatments given were four pre-starter diets fed to the chicks from day 1 to day 7; the treatments included a control diet (commercial diet), diet supplemented with glucose (control diet with 4% glucose/kg diet), semi-moist diet (control diet with 0.3 L water/kg diet) and semi-moist diet with glucose. The semi-moist diets were prepared once in two days with inclusion of an anti-mould agent and was stored in closed containers. Feed and water were provided ad libitum. Two birds from each treatment group were randomly slaughtered at age of 42 days and the carcass evaluated. Birds on control and glucose supplemented diets had better FCR in the first week compared to birds on semi-moist diet. Feeding chicks with semi-moist diet supplemented with glucose showed better FCR (P<0.05) and the highest body weight gain compared to the other treatment groups at week 6, followed by birds in the control group. Mean weight of abdominal fat (47.31 versus 29.84 g) were also significantly (P<0.05) higher for birds fed with semi-moist diet supplemented by glucose. However, there was no significant (P>0.05) different in other organ weights (liver, heart, intestine and gizzard) and subcutaneous fat. It may be concluded that semi-moist pre-starter diet with inclusion of glucose would result in broiler chicken with higher body weight gain and lower visceral fat deposition at the end of the rearing period (six weeks). However, for the morphometric analysis, control diet treatment have the tallest villi height.